PENERAPAN MEDIA VISUAL MOBILE LEARNING BERBASIS COMIC ANDROID GUNA MENINGKATKAN MOTIVASI BELAJAR SISWA PADA MATERI KALOR DAN PERPINDAHANNYA - Ratna Eka Yulianti; Dyah Astriani; Ahmad Qosyim (Jurusan IPA, Fakultas Matematika dan Ilmu Pengetahuan Alam, Universitas Negeri Surabaya, 2021)
The purpose of this study was to calculate the motivation of the students in using Android comic learning media. The research subjects used was the students of class VII E as an experiment group and class VII C as a control group at SMPN 1 Sidoarjo by using cluster random sampling technique where the subjects were randomly selected. The type of this research was quantitative. The technique of collecting the data on the student learning motivation through the ARCS type motivation questionnaire was given twice which was before and after the treatment. N-Gain was used to analyze the results of the ARCS type motivation questionnaire. The results of student motivation showed that the motivation of the experimental group was greater than the control group. The mean score of N-gain in the experimental class was 0.65 in the moderate category, while in the control class the mean score of N-Gain was 0.29 in the low category, so it can be concluded that using android comic learning media on heat material and its displacement was effective to use that can increase the students learning motivation.